2014
DOI: 10.1007/s00264-014-2296-z
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated premature stress-induced senescence of young annulus fibrosus cells of rats by high glucose-induced oxidative stress

Abstract: Purposes Diabetes mellitus (DM) is thought to be an important aetiological factor in intervertebral disc degeneration. A glucose-mediated increase of oxidative stress is a major causative factor in development of diseases associated with DM. The aim of this study was to investigate the effect of high glucose on mitochondrial damage, oxidative stress and senescence of young annulus fibrosus (AF) cells. Methods AF cells were isolated from four-week-old young rats, cultured, and placed in either 10 % FBS (normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 32 publications
(52 reference statements)
3
58
0
Order By: Relevance
“…Previous epidemiological studies reported that DM patients exhibit a higher incidence of disc degenerative diseases than patients without DM, and DM patients with disc degenerative diseases are much younger than non-DM patients [4, 7, 8]. Notably, several basic researchers demonstrated that high glucose accelerated disc cell senescence in vitro [9, 10]. These findings suggest that a high glucose environment reduces the healthy status of disc NP cell biology.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous epidemiological studies reported that DM patients exhibit a higher incidence of disc degenerative diseases than patients without DM, and DM patients with disc degenerative diseases are much younger than non-DM patients [4, 7, 8]. Notably, several basic researchers demonstrated that high glucose accelerated disc cell senescence in vitro [9, 10]. These findings suggest that a high glucose environment reduces the healthy status of disc NP cell biology.…”
Section: Introductionmentioning
confidence: 83%
“…NP cells (NP group), NP-N-CDH-NC cells (NP-N-CDH-NC group) and NP-N-CDH cells (NP-N-CDH group) were cultured in 10% FBS culture medium with 0.2 M glucose for 3 days under standard conditions (37°C, 20% O 2 and 5% CO 2 ) to investigate the effects of N-CDH overexpression on NP cell senescence under the high glucose condition. The high glucose concentration used was based on previous studies [9, 10]. …”
Section: Methodsmentioning
confidence: 99%
“…159 NF-kB signaling is known to play a critical role in a cell's response to inflammation and damage, and an increase in its activity has been connected to IDD with accumulated oxidative stress. 129,139,159,160 Pharmacologic and genetic systemic inhibition of NF-kB activity has been shown to reduce associated IDD in a mouse model. 141 Symptomatic discs have been shown to have higher levels of pro-inflammatory cytokines, TNF-α, IL1β, IL-6, and IL-8, which are considered be associated with the NF-kB pathway.…”
Section: Oxidative Stress and Deregulated Signalingmentioning
confidence: 99%
“…133,134 With mitochondrion dysfunction as a known source of excessive ROS production, the role of mitochondrion-dependent ROS has been described in various disc cells including human and rat NP and AF cells. [135][136][137][138][139] And more specifically, excessive ROS production has been reported in degenerative discs of rats. 140 Several studies have shown hydrogen peroxide to down regulate the expression of collagen type II and aggrecan in both human and rat disc cells.…”
Section: Oxidative Stress and Deregulated Signalingmentioning
confidence: 99%
“…Increasing levels of ROS have been associated with increasing levels of DDD, inhibition of proliferation of NP cells, and activation of the senescent signal pathways to induce cell cycle arrest of NP cells. [33][34][35] Reducing nutrient supply and growth factors (Insulinlike Growth Factor (IGF-1), Fibroblast Growth Factor (FGF), Platelet Derived Growth Factor (PDGF)) at the level of the IVD has been shown to increase rates of disk cell senescence. Specifically, IGF-1 has been shown to prevent disk cell senescence induced by oxidative damage.…”
Section: Cell Senescencementioning
confidence: 99%